Nitrogen Fertilization of Direct-Seeded Flooded Vs. Transplanted Rice. I. Nitrogen Uptake, Photosynthesis, Growth and Yield - Schnier, H.F.; Dingkuhn, M.; De Datta, S.K.; Mengel, K.; Faronilo, J.E. (Wiley, 1990)
Direct‐seeded flooded rice (Oryza sativa L.) culture is becoming an increasingly popular alternative to transplanting in some regions of Asia. Two field studies were therefore conducted to compare the growth patterns of wet‐row‐seeded and transplanted ‘IR64’ rice as affected by rate of N fertilizer application (0 and 90 kg N ha−1 in 1987 and 0, 30, 60, 90, 120, and 150 kg N ha−1 in 1988). Row‐seeded rice exhibited faster crop establishment and a more productive vegetative growth phase, because transplanting shock was absent and tiller number greater. Leaf area index was greater in row‐seeded than in transplanted rice. During the reproductive and ripening stages, lower foliar N concentration depressed canopy CO2 assimilation and crop growth rate of row‐seeded rice. Lower foliar N concentration was caused by dilution and not by reduced uptake. Greatest grain yield was 9.0 Mg ha−1 with 120 kg N ha−1 applied in transplanted rice and 150 kg N ha−1 in row‐seeded rice. Yield response to applied N was significant up to 60 and 90 kg N ha−1 in transplanted and row‐seeded rice, respectively. The harvest index was lower in row‐seeded than in transplanted rice at all N rates. Row‐seeded rice had a higher N demand and an inferior ability to convert high biomass production into grain yield as compared with transplanted rice. Alternative genotypes with reduced tillering ability and limited leaf area production during the reproductive stages may improve the performance of tropical wet direct‐seeded rice.